ENDOSCOPIC ENDONASAL TRANSSPEHNOIDAL APPROACH FOR REMOVAL OF SELLAR AND PARASELLAR BRAIN LESIONS – ADVANTAGES AND LIMITATIONS - Kamiloski, Tomi Viktor; Rendevski, Vladimir; Dodevski, Ace; Zupanovski, Aleksandar; Shuntov, Blagoj (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
The endoscopic endonasal transsphenoidal surgical approach is a minimally invasive neurosurgical procedure in the treatment of sellar and parasellar brain lesions. According the literature reports, the results are comparable or even better with respect to surgical radicality. This approach is associated with reduced morbidity, faster recovery times, and superior visualization of the surgical field, making it an increasingly preferred option in neurosurgery. The aim of this study is to update the knowledge and the information of the transnasal transphenoidal surgical approach and treatment of brain lesions, its application and outcomes, advantages and disadvantages of this technique.Increasing experience with this technique can decrease rates of complications. A trend towards a lower total complication rate with increasing study size was observed. The review of complications of transsphenoidal surgery showed that transsphenoidal surgery seems to be a reasonably safe procedure, with a mortality rate of less than 1%, with a significant number of complications which were more frequent in less experienced surgeons. Many researches showed similar results when analyse the complications after endonasl endoscopic surgery. Compared to more traditional surgical techiques, endonasal transphenoidal endoscopy showed lower rate of neurological complications, greater improved in visibility, moderate rate of endocrinological disturbance and higher rate of cerebrospinal leakage. Main advantages of the endonasal approach are the direct access to the sellar region without brain retraction and a straight forward procedure. Major drawbacks are the increased risks for postoperative CSF fistulas, sinonasal complications and the limited access to lateral structures.Modern technical innovations in endoscopic endonasal skull base surgery like enhance the safety, efficacy, and overall success of the endoscopic transnasal approach to sellar, suprasellar and other skull base brain lesions. Keywords: Endoscopic, endonasal, transsphenoidal, brain lesions, neurosurgical.